Micronutrient-rich food consumption, intra-household food allocation and child stunting in rural Nigeria - Fadare, Olusegun; Mavrotas, George; Akerele, Dare; Oyeyemi, Motunrayo (Cambridge University Press, 2019)
Children from rural households are often deprived of adequate micronutrient intakes either from food or supplementation. The present study examines: (i) the determinants of households’ micronutrient-rich food consumption; and (ii) the combined effect of vitamin A supplementation and micronutrient-rich food consumption on child stunting in households with different food allocation patterns.Cross-sectional study. Households’ micronutrient-rich food consumption frequency and vitamin A supplementation were used as a proxy measure for child micronutrient intakes. Intra-household food allocation patterns were assessed from caregivers’ perception of the disparity in food distribution within the household. Descriptive statistics and logistic regression were employed in analysing the study’s objectives.Rural communities in Kwara State, Nigeria.Included 419 children aged 6–59 months and 413 households.Owning small livestock and a refrigerator, knowledge of micronutrient-rich foods and higher parental education had strong associations with households’ micronutrient-rich food consumption. Children from households that consumed micronutrient-rich foods and received more diverse diets were less likely to experience stunting. The combined effect of micronutrient-rich food consumption and vitamin A supplementation was stronger on the likelihood of stunting reduction than the separate effect of each.Assets ownership, human capital and knowledge of micronutrient-rich foods improve consumption of micronutrient-rich foods among the study population. Micronutrient supplementation to children with poor access to micronutrient-rich foods may not substantially enhance child growth unless reinforced through consumption of micronutrient-rich foods. Fruit and vegetable gardening, livestock holdings and nutrition education to parents should be integral parts of community nutrition programming.